Correntes e massas de água no complexo estuarino de São Marcos e plataforma continental adjacente - CARVALHO, Kerlem Luina Vinhas (2023)
This study aimed to characterize the temporal variation of circulation and water masses in the São Marcos Estuarine Complex (SMEC) and adjacent Continental Shelf (PC), in different rainfall periods. Data were acquired throughout along the anchorages were carried out during the dry season of 2020 and the rainy season of 2021, under spring tide conditions. Current velocity measurement was obtained with the aid of a 500 MHz frequency sensor ADCP (Sontek/YSI) and state variables and mass field was obtained using a CTD (EXO2 / YSI) as a stand-alone unit. The results obtained from the circulation showed that the regions presented bidirectional flow and with dominance of ebb currents, intense currents of up to 2 m s-1 in the estuarine anchorages attributed to the SMEC funneling and the reduction in the CP velocities attributed to its width. Temperatures ranged from 27.5 to 30.7 ºC and salinities ranged from 18.3 to 36.6 g kg -1 The analysis of thermohaline indices suggests the presence of three water masses: during the dry season an Estuarine Water (AE) and Coastal Water (AC) and during the rain a Front Water (AF) in addition to AE and AC. For the transport of salt, the estuarine anchorages presented themselves as salt exporting regions, while the CP anchorages presented themselves as salt importers. The Richardson layer number indicated behaviors of moderate to high stability in the water column possibly associated with tidal currents, and through the stratification-circulation diagram the regions were characterized as type 1a (well mixed and weakly stratified) and 2a (partially mixed and with weak vertical stratification). The study considered that the sampling carried out represents another step in the understanding of estuarine systems and the changes that occurred in the drainage basin.